2008
DOI: 10.1007/s12055-008-0052-y
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial infections in infants and children after cardiac surgery

Abstract: Objective: To identify the incidence, characteristics and risk factors of nosocomial infections (NIs) in infants and children undergoing open heart surgery, a prospective observational study. Methods: One hundred consecutive infants and children < 2 yrs of age undergoing open heart surgery (OHS) between March 2007 and December 2007 were included in the study. Samples for blood, endotracheal and urine culture were drawn daily during intensive care unit (ICU) stay. Cultures from endotracheal tube, central venous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 14 publications
3
11
0
7
Order By: Relevance
“…There was also statistically significant increase in ventilation duration, ICU and hospital stay, and mortality in patients with HAI compared to noninfected patients, same was observed by other studies too. [6111318] We also observed that the antibiotic resistance profile has changed over time for the worse with more and more drug-resistant pathogens, with more Gram-negative bacteria causing HAI, as has been reported by MacVane. [19] This suggests a need to decrease sources of infections such as invasive device days and provide more effective antibiotic prescribing practices to have the greatest overall impact on HAIs.…”
Section: Discussionsupporting
confidence: 64%
“…There was also statistically significant increase in ventilation duration, ICU and hospital stay, and mortality in patients with HAI compared to noninfected patients, same was observed by other studies too. [6111318] We also observed that the antibiotic resistance profile has changed over time for the worse with more and more drug-resistant pathogens, with more Gram-negative bacteria causing HAI, as has been reported by MacVane. [19] This suggests a need to decrease sources of infections such as invasive device days and provide more effective antibiotic prescribing practices to have the greatest overall impact on HAIs.…”
Section: Discussionsupporting
confidence: 64%
“…The low incidence of HAIs in our study, compared to the Indian cohort [5], may reflect strict implementation and adherence to the institutional Infection Control (IC) policy including strict visit regulations (one parent at a time), hand hygiene and an 1:1 nurse-to-patient ratio in high dependency/intensive care areas. An inverse correlation between HAI rates and nursing hours to patient day ratio had been reported in a previous cohort [2].…”
mentioning
confidence: 67%
“…In the hospital setting of developing countries, where sub-optimal infection control and resource utilization may adversely affect surgical outcome, HAI rates are predictably higher (e.g 49% in India) than those in developed countries where rates range from 5.5% to 30.8% [2,3,4,5]. We report the frequency of HAIs and the associated case fatality rate among post-cardiac surgery pediatric patients admitted to the cardiac intensive care unit (CICU), at the Aga Khan University (AKU), Karachi, Pakistan between January 2008 and June 2009.…”
mentioning
confidence: 99%
“…The more complicated the operation, the longer the operation time, and the worse the outcome of the patient [26]. Duration of surgery and surgical complexity score are all risk factors of nosocomial infections in infants and children undergoing open heart surgery [20,27]. The possible cause is that the risk of bacterial contamination and cell damage increases at the surgical site as the operation time increases.…”
Section: Discussionmentioning
confidence: 99%